Sovereignty and Human Rights: Examining Sustainable Plantation Enterprises in Indonesia - Hairan, Hairan; Negara, Tunggul Anshari Setia; Koeswahyono, Imam; Sugiri, Bambang (Administrative and Environtmental Law Review, 2024)
The Sovereignty Principle in the Plantations Law legalizes dynamics that disproportionately empower plantation companies while disenfranchising indigenous peoples. Under this principle, plantation permits are granted to companies, not indigenous communities, limiting the latter's involvement in mandatory deliberations set by the law. Consequently, indigenous peoples are coerced into relinquishing their lands in exchange for compensation, leading to the erosion of their collective land rights. This practice is at odds with the protections intended under Article 28D Paragraph (1) and Article 28H Paragraph (2) of the 1945 Constitution of Indonesia, which safeguard collective rights to property. The lack of political will to recognize and protect these rights suggests a troubling disregard for the existence and sovereignty of indigenous peoples.